Analisa Performa Dessicant Dehumidifier Terhadap Bukaan Damper Pre-Cooling Dengan 10 – 100% Bukaan Pada Aplikasi Clean Room PT Marin Liza Farmasi - Chandra Dwiaji, Yudhi; Maulana, Ade (Indonesian Society of Applied Science, 2025)
Indonesia is a country that has a tropical climate, so the content of water vapour in the air is very high, therefore many industrial products are damaged due to high humidity, such as products with hygroscopic material characteristics, for example powder products, medicine tablets, sugar, fertilisers or products with other similar applications. The product will experience clumping so that the resulting product quality is not optimal. On the other hand, high air humidity in a controlled room is certainly very detrimental to the continuity of the production process as well as in clean room applications. Effervescent’s production room at PT Marin Liza Farmasi is an example of a clean room with temperature and RH controlled at 23°C and a water vapour content of 3.47 g/kg with RH less than 20%. If the temperature and water vapour content are not met, production cannot be carried out. The room is positively pressurised with 1177 CFM of fresh air. Damper in pre-cooling is a part that is very influential on the performance of desiccant dehumidifier. Pre-cooling dampers with openings of 10% - 100% openings will affect the value of the bypass factor and air contact factor against the evaporator cooling coil on the pre-cooling AHU, this will also affect the amount of water vapor partial pressure which is influenced by the large temperature coming out of the pre-cooling AHU due to the influence of the evaporator coil temperature. Each damper opening will be tried and analyzed to get the best water vapor content out of the dehumidifier without disturbing the performance of other systems. The damper openings selected for the Effervescent production clean room project at PT Marin Liza Farmasi are the 50% and 60% openings that produce the best dehumidifier performance without interfering with the performance of other systems, which at these openings produce a dehumidifier outlet water vapor content of 1.12 g/kg at the 50% opening with a bypass factor in pre-cooling of 12.26% and 1.2 g/kg at the 60% opening with a bypass factor in pre cooling of 12.90%.